Impact of Technology Integration in Physical Education: A Review of Trends and Tools - Srinivasan, J. P. Desiga (AG Volumes, 2025)
Recent years have seen a sharp increase in the use of technology in physical education (PE), with the goal of improving learning results, student engagement, and long-term commitment to physical exercise. Review the many studies on the effects of integrating technology into physical education in this article. Through improved student engagement, personalisation, and performance results, technology integration in physical education has revolutionised teaching and learning, as this study demonstrates. By providing personalised training and real-time feedback, technologies like wearable fitness trackers, interactive applications, AI-powered platforms, and virtual reality enhance "cardiovascular endurance and activity levels". Technology also streamlines administrative tasks and fosters inclusive, creative, and innovative approaches to physical education. Virtual coaching, gamification, and performance tracking enable skill development and curriculum enhancement. With strategic investments and policy support, educational institutions can fully leverage technology to modernize PE programs, meet diverse student needs, and promote lifelong fitness and well-being.